Design and optimization of a cam-actuated electrohydraulic brake system. (June 2018) - Durali, Laaleh; Khajepour, Amir; Jeon, Soo
Although different types of brake-by-wire mechanism including electrohydraulic brakes, electromechanical brakes, electronic wedge brakes and distributed electrohydraulic brakes have been developed in the past two decades, there is still an increasing demand for further improvement and also for development of new brake mechanisms in the automotive industry because of the escalating requirements for higher safety and better performance. This paper proposes a novel brake-by-wire system based on the cam actuation mechanism. The proposed cam-actuated electrohydraulic brake system is a combination of an electrical component, a mechanical component and a hydraulic component. The unique feature of the proposed cam-actuated electrohydraulic brake system is that the characteristics of the motor torque amplification can be optimized by careful design of the cam shape. The overall structure of the cam-actuated electrohydraulic brake system is described, and the dynamic model of the system is developed. Optimum design of the cam-actuated electrohydraulic brake system is obtained by multi-objective optimization, and the obtained simulation results are discussed. The compactness and the self-contained characteristics of the design enable the brake system to be installed on each wheel, allowing fully independent control of each wheel for better stability control.